Interaction of hormonal and social environments in understanding body image concerns in adolescent girls. (February 2019) - Forney, K. Jean; Keel, Pamela K.; O'Connor, Shannon; Sisk, Cheryl; Burt, S. Alexandra; Klump, Kelly L.
Abstract: During adolescence, peer approval becomes increasingly important and may be perceived as contingent upon appearance in girls. Concurrently, girls experience hormonal changes, including an increase in progesterone. Progesterone has been implicated in affiliative behavior but inconsistently associated with body image concerns. The current study sought to examine whether progesterone may moderate the association between perceived social pressures to conform to the thin ideal and body image concerns. Secondary analyses were conducted in cross-sectional data from 813 girls in early puberty and beyond (ages 8–16) who completed assessments of the peer environment, body image concerns, and progesterone. Models for mediation and moderation were examined with BMI, age, and menarcheal status as covariates. Belief that popularity was linked to appearance and the experience of weight-related teasing were both positively associated with greater body image concerns, but neither was associated with progesterone once adjusting for covariates. Progesterone significantly interacted with perceived social pressures in predicting body image concerns. At higher progesterone levels, appearance-popularity beliefs and weight-related teasing were more strongly related to body image concerns than they were at lower progesterone levels. Findings support a moderating role for progesterone in the link between social pressures and body image concerns in girls. This study adds to a growing literature examining how girls' hormonal environments may modulate responses to their social environments. Longitudinal and experimental work is needed to understand temporal relations and mechanisms behind these associations. Highlights: Both the peer environment and hormones may contribute to body image concerns. Progesterone moderates the association between peer approval and body image. Higher progesterone levels may raise vulnerability to peer influence on body image.